2002
DOI: 10.1248/bpb.25.1351
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Influx Transport Mechanism of Pentazocine at the Blood-Brain Barrier in Rats Using the Carotid Injection Technique.

Abstract: Pentazocine (PTZ), a narcotic-antagonist analgesic, is widely used in the management of patients with postoperative pain or initial carcinogenic pain.1) PTZ is a cationic drug having physicochemical properties of high lipophilicity, 2) and immediately reaches the brain in rats when the drug is administered parenterally. 3,4) In rats, brain-plasma concentration ratio is relatively constant, and PTZ concentration in the brain is much higher than that in the corresponding plasma. 5,6) The blood-brain barrier (BBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…From the data obtained with the BUI method (see ''The in vivo permeability''), another kinetic parameter, the brain uptake rate (J [nt -1 m -1 ]), could be calculated as (Pardridge 1995;Suzuki et al 2002):…”
Section: The Brain Uptake Ratementioning
confidence: 99%
“…From the data obtained with the BUI method (see ''The in vivo permeability''), another kinetic parameter, the brain uptake rate (J [nt -1 m -1 ]), could be calculated as (Pardridge 1995;Suzuki et al 2002):…”
Section: The Brain Uptake Ratementioning
confidence: 99%
“…The in vivo uptake of pentazocine, a narcotic-antagonist analgesic, by rat brain was significantly inhibited by lidocaine, imipramine and propranolol, as well as by H1 antagonists such as mepyramine and diphenhydramine. 71 Pentazocine, in spite of efflux transport by P-glycoprotein at the BBB, is also highly distributed into brain by a carriermediated transport system that may widely recognize cationic drugs.…”
Section: Other Drugsmentioning
confidence: 99%
“…2,3) These results may be explained by the saturation of the efflux transport from the brain capillary endothelial cells.…”
mentioning
confidence: 97%
“…We recently demonstrated that PTZ is transported predominantly via a carrier-mediated influx system at the blood-brain barrier (BBB) in rats, using both the brain uptake index (BUI) method 2) and an in situ brain perfusion technique.…”
mentioning
confidence: 99%